2023
DOI: 10.1029/2022ja030745
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Isolated and Storm‐Time Ion Injections

Abstract: The injection of energetic particles is considered as one of the basic characteristics at the onset of magnetospheric substorm. Dispersionless injection refers to the sudden increase in the flux of particles (tens to hundreds of keV) simultaneously in different energy channels. It has been studied extensively (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It is well known that the thermal anisotropy of ring current 10-100 keV ions provides free energy for the EMIC wave instability. Plasma injected or transported into nightside of the inner magnetosphere (Dai et al, 2015(Dai et al, , 2014He et al, 2012He et al, , 2016He et al, , 2023Xiong et al, 2022) and pressure enhancement at dayside (Remya et al, 2015;Tsurutani et al, 2016) could both change the distribution of ring current. Substorm ion injections associated with H + -band EMIC waves at L between 5 and 6 have been studied (Jun et al, 2019;Kim et al, 2021;Remya et al, 2018], however the isolated ion injections during substorms have been rarely observed in the inner zone.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is well known that the thermal anisotropy of ring current 10-100 keV ions provides free energy for the EMIC wave instability. Plasma injected or transported into nightside of the inner magnetosphere (Dai et al, 2015(Dai et al, , 2014He et al, 2012He et al, , 2016He et al, , 2023Xiong et al, 2022) and pressure enhancement at dayside (Remya et al, 2015;Tsurutani et al, 2016) could both change the distribution of ring current. Substorm ion injections associated with H + -band EMIC waves at L between 5 and 6 have been studied (Jun et al, 2019;Kim et al, 2021;Remya et al, 2018], however the isolated ion injections during substorms have been rarely observed in the inner zone.…”
Section: Summary and Discussionmentioning
confidence: 99%